2002
DOI: 10.1152/ajprenal.00351.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of prostaglandin EP2receptors to renal microvascular reactivity in mice

Abstract: The present studies were performed to determine the contribution of EP 2 receptors to renal hemodynamics by examining afferent arteriolar responses to PGE 2, butaprost, sulprostone, and endothelin-1 in EP 2 receptor-deficient male mice (EP2Ϫ/Ϫ). Afferent arteriolar diameters averaged 17.8 Ϯ 0.8 m in wild-type (EP 2ϩ/ϩ) mice and 16.7 Ϯ 0.7 m in EP2Ϫ/Ϫ mice at a renal perfusion pressure of 100 mmHg. Vessels from both groups of mice responded to norepinephrine (0.5 M) with similar 17-19% decreases in diameter. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 44 publications
3
36
1
Order By: Relevance
“…In hydronephrotic kidneys, we mapped the PGE 2 response along the preglomerular tree, finding vasoconstriction of proximal ILAs, while distal ILAs and AAs only manifested PGE 2 -induced vasodilation. This latter observation is consistent with the response of AAs observed in most other studies (4,8,24), although PGE 2 -induced vasoconstriction of these vessels has also occasionally been reported (9,24). In addition, we found that intermediate ILAs displayed a biphasic response to increasing concentrations of PGE 2 , i.e., vasodilation followed by vasoconstriction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In hydronephrotic kidneys, we mapped the PGE 2 response along the preglomerular tree, finding vasoconstriction of proximal ILAs, while distal ILAs and AAs only manifested PGE 2 -induced vasodilation. This latter observation is consistent with the response of AAs observed in most other studies (4,8,24), although PGE 2 -induced vasoconstriction of these vessels has also occasionally been reported (9,24). In addition, we found that intermediate ILAs displayed a biphasic response to increasing concentrations of PGE 2 , i.e., vasodilation followed by vasoconstriction.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, EP1 receptor labeling was predominantly found at the level of the endothelium. Tang et al (24), who in contrast to our and various other studies (4,8), observed afferent arteriolar constriction to high PGE 2 concentrations, also found that this response was mediated via EP3 receptors. We observed that when isolated proximal ILAs were pretreated with a selective EP1 receptor antagonist, PGE 2 -induced vasoconstriction was not inhibited but rather potentiated, indicating that EP1 receptor activation stimulates a vasodilator process.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The perfused juxtamedullary nephron preparation was used to assess renal microvascular reactivity as described previously (54). Male C57BL/6 mice weighing 20-25 g were used.…”
Section: Figurementioning
confidence: 99%
“…Mice were anesthetized with thiobutabarbital (inactin; 100 mg/kg i.p.). The kidney was removed and immediately isolated and perfused in vitro with a physiological salt solution and mixture of l-amino acids (54). The juxtamedullary vasculature was isolated for study, and an afferent arteriole was monitored continuously by videomicroscopy.…”
Section: Figurementioning
confidence: 99%